Drug Repositioning Screen on a New Primary Cell Line Identifies Potent Therapeutics for Glioblastoma - Senbabaoglu, Filiz; Aksu, Ali Cenk; Cingoz, Ahmet; Seker-Polat, Fidan; Borklu-Yucel, Esra; Solaroglu, İhsan; Bagci-Onder, Tugba (Frontiers in Neuroscience, 2020)
Glioblastoma is a malignant brain cancer with limited treatment options and high mortality rate. While established Glioblastoma cell line models provide valuable information, they ultimately lose most primary characteristics of tumors under long-term serum culture conditions. Therefore, established cell lines do not necessarily recapitulate genetic and morphological characteristics of real tumors. In this study, in line with the growing interest in using primary cell line models derived from patient tissue, we generated a primary glioblastoma cell line, KUGBM8 and characterized its genetic alterations, long term growth ability, tumor formation capacity and its response to Temozolomide, the front-line chemotherapy utilized clinically. In addition, we performed a drug repurposing screen on the KUGBM8 cell line to identify FDA-approved agents that can be incorporated into Glioblastoma treatment regimen and identified Topotecan as a lead drug among 1200 drugs. We showed Topotecan can induce cell death in KUGBM8 and other primary cell lines and cooperate with Temozolomide in low dosage combinations. Together, our study provides a new primary cell line model that can be suitable for both in vitro and in vivo studies and suggests that Topotecan can offer promise as a therapeutic approach for glioblastoma.